Psittacanthus longerectus (Loranthaceae), a new showy species from Colombia (2014)
ABSTRACT: We describe Psittacanthus longerectus (Loranthaceae), a species so far only known from Antioquia (Colombia) and discuss the taxonomic af nities of the new species with P. acinarius and P. cyclophyllus. Psittacanthus longerectus is characterized by having cordate leaves, erect branches, and terminal inflorescences.